Sibak midnight dancers - Chionglo, Mel; Lee, Ricardo (Viva Video Inc., 2007)
Three young and good-looking brothers live with and support their parents in Manila; they dance at the male Club Exotica and work as "call boys." Joel has a wife and child; he and Dennis are saving money to buy back lost family land. Sonny has dropped out of university and sees dancing as a way to make money for now. Joel has a regular boyfriend as well; Sonny spends time with Michelle, a transvestite; Dennis and his pals steal car radios. When their nanay takes in a homeless youth who is not what he appears to be, a chain of events is set in motion that brings tragedy. Is there any salvation in this late-night world of "macho dancing" and prostitution?